Investigating (possible) tensions and possibilities of decolonising history curriculum as a locus to foster inclusive education in South African schools - Shabangu, Bongani (My University, 2022)
Today, in the 20th-century, colonialism survives through coloniality. That means the traits of colonialism such as, amongst others, dominance and subjugation are maintained through coloniality, masquerading as modernity. It is in light of this view that curriculums in the Global South still perpetuate domination. Therefore, this thesis investigates how colonialism and coloniality have been perpetuated through the history curriculum. The investigation focuses both on the colonial apartheid epoch and post-apartheid society. Hence, the apartheid history syllabus and also the post-apartheid history curriculums namely, the Revised National Curriculum Statements (RNCS), National Curriculum Statements (NCS), and Curriculum Assessment Policy Statements (CAPS) were investigated. A part of the findings suggests that history as a school subject has been used as a political tool to perpetuate racism, sexism, exclusion, alienation, negation, and domination. Hence, the need to decolonize and foster inclusive education emerges from the fact that the history curriculum is still exclusive of the LGBT+ community, ‘people with impairments indigenous people, local people, and women`s historical discourses. In essence, the thesis examines the epistemological implication of decolonizing and fostering inclusivity in the history curriculum. A meta-theoretical framework comprised of positivism, epistemological realism, and postmodernism was deployed as a tool to understand the knowledge that is envisaged by decolonization and inclusive education. The meta-theoretical framework revealed that decolonization and inclusive education are favored by the multiplicity of knowledge as opposed to the universality of knowledge. As a point of exit, the thesis proposes a new model that can be used to decolonize and foster inclusivity in the history curriculum
A research report submitted in fulfillment of the requirements of Masters of Education to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, 2022